AI and Sustainability - Mungse, Sahil; Longani, Kirti Dang (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of artificial intelligence (AI) in promoting sustainability efforts worldwide. By analyzing various global initiatives from corporations like Apple, Alibaba, and Tata, we assess AI's impact on environmental sustainability and community trust. The adoption of AI technologies has been pivotal in optimizing resource use, reducing emissions, and enhancing product lifecycle management, thus contributing significantly to sustainable practices. Through qualitative analysis of corporate reports, social media campaigns, and sustainability disclosures, this paper highlights how AI-enabled solutions foster significant advancements in achieving the Sustainable Development Goals (SDGs).